Who is watching who? Regulation of media and freedom of expression in Uganda : a critical analysis of the Press and Journalists Act of 1995 - Jjuuko, Frederick W. (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.